Troika of Adult Learners, Lifelong Learning, and Mathematics : Learning from Research, Current Paradoxes, Tensions and Promotional Strategies /: Learning from Research, Current Paradoxes, Tensions and Promotional Strategies. ([2016]) - Safford-Ramus, Katherine; (Professor of education), Misra, Pradeep Kumar; PhD, Maguire, Terry
No abstract available